The Indonesian version of volunteer functions inventory: Its validity and reliability - Rukmini, Elisabeth; Assegaf, Raychana (Journal of Education and Learning (EduLearn), 2024)
The volunteer function inventory (VFI) is an assessment tool to measure individual volunteer motivation. VFI measures individual motivation to volunteer by examining the functional motives of each volunteer. This research aimed to adapt the VFI to the Indonesian language. VFI consists of 30 items divided into five dimensions. This study utilized a non-experimental quantitative research method. Samples were acquired by accidental random sampling with N = 176. In this study, reliability testing was carried out with items and dimensions of Cronbach's α. Validity tests were examined using construct validity and item analysis. The results of the Indonesian version of VFI showed high reliability and validity. Besides, the item analysis also shows that the quality of each item is excellent. The Indonesian version of VFI will be suitable for various education fields in Indonesia to measure the students' voluntary willingness in community development activities, for example, in measuring the impact of volunteerism in the Merdeka Belajar Kampus Merdeka (MBKM) social activities and other activities within the communities.